BIOTA PERAIRAN DI AREA PERTAMBANGAN EMAS PT. NATARANG MINING, LAMPUNG SELATAN - Agus Priyono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
Dependence of the diversity of aquatic biota with water quality is typical of interaction and mutual influence. Various development activities in a watershed is now being polluted waters. Gold mining activities as open-pit mining activities have a high potential for pollution, especially water turbidity due to sediment erosion at the site of drilling / excavation of land and other open land. Problem of pollution control efforts, particularly in the area of Natarang Mining L.td should do well because in these areas flows Samuong River and its tributaries, which still has a high diversity of aquatic biota. The trend increase in water turbidity, especially seen in the rainy season in Semuong River and its tributaries which in the long term could reduce the density and diversity of aquatic biota, whether plankton, benthos and fish. Keyword: Natarang Mining L.td, aquatic biota , pollution, Semuong river